Wheel/Rail Contact Stress Evaluation by Means of The modified Strip Method - Lack, Tomas; Gerlici, Juraj (Communications - Scientific Letters of the University of Zilina, 2013)
The Strip Method is often used for rail/wheel contact area and contact normal stress evaluation. The paper deals with the computational time saving procedure when the computation accuracy is guaranteed. We included the local coordinate system with a presupposed semi-circular course of the normal stress for the purpose of the integral that is necessary for deformation in the middle of individual strips evaluation. The integral is solvable analytically. The input parameters for individual parts of splines and individual strips expression are possible to insert after analytical solution.
Keywords: wheel/rail contact; contact stress evaluation; modified strip method; optimized computation procedure